(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2013)
Can we still consider Lukács as a model of the “universalist” intellectual? And, in the geopolitical study of cinema, does the concept of totality have a relevant applicability? The matter of the legacy of Lukács’ method, especially in Jameson’s work, implies an insistent focus on his work, a re-reading and a survey of his fundamental elements, for it is precisely in what could be named his “method” that the unity of his project and his particular vision could recover their shape. Lukács’ writing on realism, Marxism and literary criticism, his contributions on the history of aesthetics, the prolegomena to a Marxist aesthetics and other parts of his work, would let us clarify some fundamental problems. This article questions a new proposition: the reviving of film studies by a non-dogmatic “come back” to the remaining lessons of Lukács and the possibility of their practice in the postcolonial studies.